Laboratory Investigation on Key Technological Parameters of Brick Concrete Recycled Coarse Aggregate Strengthened by Negative Pressure - Liu, Hongzhe; Zhao, Zhizhong; Yang, Zhenyu; Wang, Risheng; Xu, Meng (Frontiers in Materials, 2022)
The strengthening application of brick concrete recycled coarse aggregate (BCRCA) has become a “troublesome issue.” In this sense, an in-depth study on the strengthening method of BCRCA is needed. In order to improve the strengthening effect of BCRCA and perform the large-scale application of brick concrete waste, the strengthening method of BCRCA was investigated. Briefly, the performance of BCRCA was initially analyzed. Then, the pore characteristics of BCRCA were tested by CT scanning technology. The evaluation index of filling saturation was proposed. Finally, the BCRCA was strengthened by the negative pressure, and the influences of key parameters such as negative pressure, negative pressure time, negative pressure temperature, and stirring times on the strengthening effect were investigated. The test results showed that the best performance can be obtained by using the following parameters: negative pressure from −55 kPa to −80 kPa, the negative pressure time from 6 to 14 min, the negative pressure temperature from 40 to 80°C, and the stirring times from 1 to 4 times. Combined with the influence of negative pressure strengthening process parameters on filling saturation, it can be determined that a negative pressure of −75 kPa, a negative pressure time of 12 min, and a negative pressure temperature of 70°C with two times of stirring were the best negative pressure strengthening parameters. The unconfined compressive strength and indirect tensile strength reached 4.9 and 0.55 MPa, respectively, when the reinforced BCRCA was used for the cement-stabilized macadam. Therefore, the negative pressure strengthening process parameters determined in this study can achieve a good strengthening effect.